2013
DOI: 10.1007/s12020-013-9888-z
|View full text |Cite
|
Sign up to set email alerts
|

Could zinc supplementation improve bone status in growth hormone (GH) deficient children?

Abstract: EditorialReduced bone mineral density (BMD) and increased fracture rate have been reported in subjects with either childhood or adult onset growth hormone (GH) deficiency (GHD), more severe in childhood onset GHD [1,2]. A longer gap in GH replacement in adults with childhood onset GHD is associated with a lower bone mineralization and GH replacement has been suggested having a critical role in transition to adulthood to optimize bone accrual [3]. Furthermore, also a delay in starting GH replacement in GHD adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…With addition of zinc supplementation to calcium and vitamin D (Group B), the gain in bone mineral content was further enhanced. Prodam et al (2013) have suggested a need for a longitudinal study to assess the effect of nutritional supplementation on the bone parameters in GH-treated GHD children [2]. In this letter, we report the findings of the follow-up of these children 1-year post-supplementation.…”
mentioning
confidence: 89%
“…With addition of zinc supplementation to calcium and vitamin D (Group B), the gain in bone mineral content was further enhanced. Prodam et al (2013) have suggested a need for a longitudinal study to assess the effect of nutritional supplementation on the bone parameters in GH-treated GHD children [2]. In this letter, we report the findings of the follow-up of these children 1-year post-supplementation.…”
mentioning
confidence: 89%
“…In the grand mineral mosaic that constitutes our bones, phosphorus emerges as a silent yet powerful architect. As the second most abundant mineral in the human body, it joins forces with calcium to craft the sturdy hydroxyapatite crystals, the essence of the bone's mineral matrix [37]. This pivotal process of bone mineralization forms the bedrock of childhood and adolescent skeletal development.…”
Section: Phosphorus Enigma In Bone Mineralizationmentioning
confidence: 99%
“…Studies investigating the intricate link between phosphorus intake and bone health have unveiled promising findings. In a captivating cross-sectional study encompassing 1,725 children, researchers revealed that higher phosphorus intake orchestrated a symphony of improved bone mineral content and heightened bone health [37]. It is a mesmerizing performance of nutrition nourishing youthful bones, a testament to the potency of phosphorus in the developmental overture.…”
Section: Phosphorus Enigma In Bone Mineralizationmentioning
confidence: 99%